Decolonizing African-american Museums: a Case Study on Two African-american Museums in the South - (:unkn) unknown (My University, 2016)
This dissertation seeks to understand how African-American museums’ exhibits help individuals gain their sense of racial identity through public memory. In an era where the United States is supposedly “post-racial” African-American museums are flourishing. As institutions serving an important role in preserving the collective memory of African-American people in the US, African-American museums evoke questions of representation within the larger US narrative that confirm the persistent saliency of race in society, and therefore continue to have a public function in maintaining and developing a racial African-American identity (Jackson 2012; Eichstedt and Small 2002; Wilson 2012; Golding 2009). My research is focused on the following question: What impacts do African-American museums have on their patrons? An exploration of museums provides a lens through which to examine larger questions around power, representation, and race in the African-American community. In order to illuminate these larger questions I utilize a decolonial framework. A decolonial framework helps me answer my research question in two ways: 1) to explain the political and economic context these museums operate in and 2) to understand the impact the museums have on the patrons’ thinking within this political and economic context.
Keywords: African American History; African American Museums; Black Public History; Critical Museology; Museums; Visitor Observation Study